Differential Maize Yield Hybrid Responses to Stand Density Are Correlated to Their Response to Radiation Reductions Around Flowering - Larrosa, Federico H.; Borrás, Lucas (Frontiers in Plant Science, 2022)
Increased stand density affects maize yields by producing changes in both numerical yield components, kernel number per plant (KNP) and kernel weight (KW). Kernel number is determined by the accumulation of ear biomass during the flowering period, while KW is determined by the sink potential established during flowering and the capacity of the plant to full fill this potential during effective grain filling. Here we tested if different short shading treatments during different stages around flowering can help discriminate genotypic differences in eco-physiological parameters relevant for maize stand density yield response and associated yield components. Our specific objectives were: i) identify hybrids with differential shading stress response, ii) explore shading effects over eco-physiological parameters mechanistically related to yield numeric components KNP and KW, and iii) test if shading stress can be used for describing genotypic differences in yield response to stand density. Objectives were tested using four commercial maize hybrids. Results indicated that KNP was the yield component most related to yield changes across the different shading treatments, and that the specific shading imposed soon after anthesis generated the highest yield reductions. Hybrids less sensitive to shading stress were those that reduced the less their plant growth rate and accumulated more ear biomass during flowering. Genotype differential susceptibility to shading stress around flowering was correlated to stand density differential responses. This indicated specific shading stress treatments are a useful tool to phenotype for differential stand density responses of commercial hybrids.